2021
DOI: 10.1136/bmjoq-2020-001120
|View full text |Cite
|
Sign up to set email alerts
|

Improving intravenous-to-oral antibiotic switch in children: a team-based audit and implementation approach

Abstract: Children in hospital are frequently prescribed intravenous antibiotics for longer than needed. Programmes to optimise timely intravenous-to-oral antibiotic switch may limit excessive in-hospital antibiotic use, minimise complications of intravenous therapy and allow children to go home faster. Here, we describe a quality improvement approach to implement a guideline, with team-based education, audit and feedback, for timely, safe switch from intravenous-to-oral antibiotics in hospitalised children. Eligibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Following recent updates to the TG, antibiotic DoT has been suboptimal, with treatment continued beyond recommended durations. The literature suggests that adherence to antibiotic prescribing guidelines can be improved through a range of strategies, including education about the use of narrow‐spectrum over broad‐spectrum antibiotics, 14 earlier intravenous to oral switching, 15 introducing AMS teams, 16 and providing aids such as posters and cards for quick referencing 12 . Whilst efforts have been made toward improving antibiotic prescribing, limited studies have demonstrated improvement in antibiotic DoT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following recent updates to the TG, antibiotic DoT has been suboptimal, with treatment continued beyond recommended durations. The literature suggests that adherence to antibiotic prescribing guidelines can be improved through a range of strategies, including education about the use of narrow‐spectrum over broad‐spectrum antibiotics, 14 earlier intravenous to oral switching, 15 introducing AMS teams, 16 and providing aids such as posters and cards for quick referencing 12 . Whilst efforts have been made toward improving antibiotic prescribing, limited studies have demonstrated improvement in antibiotic DoT.…”
Section: Discussionmentioning
confidence: 99%
“…There are several strategies to improve prescribing with potential translation to reductions in antibiotic duration of therapy (DoT). Considerable research has been carried out to demonstrate the benefits of: promotion of local guidelines, national guidelines, and formulary restrictions; 12,13 the use of aids such as cards and posters to help guide the choice of antibiotics; 12 advocacy for early narrow‐spectrum antibiotics over broad spectrum, where appropriate; 14 improving intravenous to oral antibiotic switching; 15 and fostering a culture of antimicrobial stewardship (AMS) 16 . The overall implementation of these interventions is summarised in several systematic reviews and the World Health Organization guideline for antimicrobial stewardship programs 17–19 …”
Section: Introductionmentioning
confidence: 99%
“…For the families of children requiring antibiotic therapy, the switch to oral treatment generally facilitates discharge from hospital. Treatment at home offers numerous advantages for the affected families: The parents can go back to work, and the child may resume educational training and spare time activities[ 20 ]. Furthermore, painful, and stressful events due to the insertion of intravenous catheters and complications associated with indwelling intravenous catheters are reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, an ASP including 89 European NICU from 21 countries found that GENT and AMK were the most frequently prescribed aminoglycoside with little variance in dosing as to the BNFc and Neofax reference values [ 3 ]. An Antibiotics Prevalence Survey of Australian hospitalized newborns recently found that the most prescribed antibiotic was also GENT with a median dose of 5 mg/kg/d (IQR: 4; 5) [ 22 ]. Even though the benefits of ASP are variously appreciated, a decrease of 34% (16.7 to 12.1%) in antibiotic utilization on the audit day was obtained by the Vermont Oxford Network, which involved 146 NICU participating in an internet-based quality improvement collaborative [ 23 ].…”
Section: Discussionmentioning
confidence: 99%